The role and development of strength for elite judo athletes - Ren, M.; Tian, Y.; McNeill, C.; Lenetsky, S.; Uthoff, A. (Strength and Conditioning Journal, 2023)
The Olympic combat sport of judo is characterized by high-intensity intermittent efforts to throw an opponent to the ground, pinning, or submitting them. High-level judo coaches have established neuromuscular performance as one of the key performance indicators in judo. This is likely because the judo athlete performs several neuromuscular challenges, including establishing grip dominance while engaging an opponent when standing, performing highly technical throws, and exerting dynamic and isometric contractions to control an opponent on the ground. As such, a stronger judo practitioner has an advantage over opponents with comparable technical ability. With that in mind, this review aims to examine the role different types of strength play in judo performance and provide training recommendations based on neuromuscular attributes for training elite judo athletes.